Lung cancer: 1 year experience at tertiary care centre with reference to cytodiagnostic approach - Mehta, Mansi; Gupta, Nisha; Odhwani, Jaydeep; Desai, Nandini; Santwani, P. M. (International Journal of Advances in Medicine, 2017)
Background: Lung cancer is the most common cancer incidence wise as well as leading cause of cancer related death in worldwide as well as in India. Cytological diagnosis plays an important role in patients having lung cancer. This study was conducted to evaluate sensitivity of various cytological methods in diagnosis of lung cancer, to study typing of lung cancer, age and gender wise distribution of lung cancer and its association with smoking. Methods: This study includes patients having clinical and radiological diagnosis of lung cancer. Total 150 cases of entire January 2015 to December 2015 are included. Methods obtaining samples includes, abrasive cytology by bronchoscope guided: bronchoalveolar lavage (BAL); brush cytology and bronchial washing, CT/USG guided transthoracic fine needle aspiration, trans- bronchial needle aspiration. Samples have been processed as per standard protocols and cytomorphology of samples are studied, along with these patient age, gender, and smoking habit have been recorded. Results: Sensitivity of various method: abrasive cytology by bronchoscope guided bronchoalveolar lavage (BAL); brush cytology and bronchial washing, trance bronchial needle aspiration, CT/USG guided transthoracic fine needle aspiration is 70%, 66%, 90% respectively. Adenocarcinoma is most common carcinoma followed by squamous carcinoma, having incident of 41%, 31.39% respectively. In male patient peak age is 5th decade, and in female peak age is 6th decade. Male:female ratio is 5.1:1. Adenocarcinoma is most common carcinoma is 10 times more common in non-smokers as compare to squamous cell carcinoma .But association of squamous cell carcinoma with smoking is 97%. Conclusions: CT/USG guided transthoracic fine needle aspiration method has highest sensitivity. In male patients peak age of presentation of lung carcinoma is 5th decade, and in female patient’s peak age is 6th decade. Lung carcinoma found to be more common in males than in females. Adenocarcinoma is most common carcinoma. It is 10 times more common in non-smokers as compare to squamous cell carcinoma. Association of squamous cell carcinoma with smoking is 97%.